PENGEMBANGAN BAHAN AJAR PENULISAN KARYA ILMIAH BERBASIS VOKASI - Moh Thamrin (LITERA, 2014)
This study aims to develop learning materials for vocation-based academic writing to improve polytechnics students’ academic writing skills. It employed an adapted development model by Dick and Carey. The development procedure consisted of planning, production, expert validation, practitioner validation, and field testing. The results of the study are as follows. First, the results of the expert validation showed that the learning materials were relevant to the polytechnics characteristics with an emphasis on practical matters, the presentation moves from theories to examples, steps, and practices, and the assessment is appropriate. Second, the practitioner responses show that the content, presentation, and graphic aspects are moderately good. Third, the field testing generally shows satisfactory results. Fourth, the effectiveness test shows that the learning materialsare effective to improve students’ academic writing skills.